Headquarters as hardware and software - Kevin Sharer (Journal of Organization Design, 2019)
The article proposes a framework for thinking about the role and elements of a corporate headquarters. The concept is that headquarters is both a physical place with implications for the culture and work processes of the firm and a set of processes and strategies that define how the work actually gets done and the employees and leadership groups interact. The main thesis of the piece is that to properly design and operate headquarters that these elements of both hardware and software of headquarters must be designed and operated together.
Keywords: 650; Headquarters; Culture; Work processes; Design process; Campus design; Headquarters; Culture; Work processes; Design process; Campus design